Co-crystal explosives-explosives improved characteristics - Mićin, Saša (Journal of Engineering & Processing Management, 2017)
Explosive substances are very important compounds from the point of manufacture, storage, transport and use. Research and development of secondary explosives in the previous time is intensified in order to obtain improved explosive materials is physical, chemical and explosive characteristics. One of the directions of development are research in the field of co-crystals. In this paper, present the literature results of previous studies of co-crystals of modern conventional explosives. The co-crystal of the compound represented CL-20, octogen (HMX), TKX-50, trotyl (TNT) and certain compounds of explosive to be used to a minor extent. Analysis of test results of crystal structure, intermolecular interactions, mechanical sensitivity, thermal decomposition, reaction mechanisms creation products and explosion characteristics indicate improved explosives properties in relationship to components that make it.